Addressing the Conceptual Controversy of Sustainable Intensification of Agriculture: A Combined Perspective from Environmental Philosophy and Agri-Environmental Sciences - Gustavo Cambareri; Joshua Grant-Young (Philosophies, 2018)
During the last 20 years, agronomists, environmentalists and related researchers have conveyed the need of producing enough food to satisfy the growing population demand, with minimum environmental footprint. Under this framework, the need for a “sustainable intensification„ (SI) of agriculture has arisen, being a concept deeply contested the last several years. We aim to shed some light on the matter from the point of view of both environmental philosophy and agri-environmental sciences. We found that the lack of clarity exposes the conceptual limits of SI, since its attributions are far from being extrapolated, for example, to animal production. Agricultural science should ensure that stakeholders understand the facts and implications of SI before implementing them. In addition, if understood only as either a set of practices or a sort of panacea, SI will be closer to fail for stakeholders’ expectations. Then, a key concern we have highlighted is one which should compel agri-environmental scientists and environmental philosophers alike to hold such conceptual frameworks accountable. Ensuring communities and public actors make informed choices about food security requires that shared goals between our disciplines are enacted in research, with community well-being as a core consideration of any debate regarding sustainability.